VLADIMIR PUTIN’S REGIME: THE SYSTEM OF MULTI-LAYERED POWER ELITE GROUPS - Keršanskas, Vytautas (Politologija, 2017)
There are many different explanations of how the Russia’s political system, after the collapse of the USSR, is functioning. Some argue that it can be described as a strictly centralized power vertical, authoritarian or even dictatorial model. Others suggest that the basis of the system lay in the power of elite groups or media control (mediocracy). However, the different perspectives share same assumption: the essential role in the Russian political system is played by various power elite groups; thus, their analysis helps one to understand the functioning of the regime more profoundly. The analyses of Post-Communist Russia’s elite are based on the main assumptions of the theories of power elite. It means that not only relations and interactions between various power groups are analyzed, but also the links between the concentration of power in specific groups with the post-Communist Russia transformation process. However, Russia’s political system is a “black box” that is very hard to open and acknowledge. Therefore, even an analysis of the elite groups can only give partial answers to the study of its political system. Firstly, an overview of the formation of the political elite in post-Communist Russia is presented. The main driving forces of this process are also presented. It allows the author to frame the main assumptions of the Russian power elite, especially during Vladimir Putin’s rule. Based on the suggested Russia’s political system explanation and the power elite grouping model, an overview of the main current actors, both systematic and outside-the-system, formal and informal, are presented. Systematic actors include actors from the closest circle of Vladimir Putin to the ones who simulate opposition forces. Meanwhile, an analysis of the actors outside the system also suggest the main means by which they are eliminated from the political system. The author suggests a multi-layered Russia’s power elite analysis model. The inner circle, which consists of individuals closest to V. Putin, is formed from the most loyal and long-lived sidekicks. They hold the most power in their hands despite their formal positions in the state. It can be understood as a “buffer zone” that absorbs the influence of other, competing elite groups. The second circle is formed from two groups. The “Politburo” involves both the actors from the inner circle and at that time the most influential players outside it. Another group is of formal officers/technocrats who do not have huge influence on the President’s decisions but are needed to preserve the regime – they are implementers, not decision-makers. Finally, the last circle is formed from other players, such us controlled opposition or regional leaders. Further, the main principles of the functioning of the regime are presented as well as the influence and rise of specific groups, such as the siloviki, are discussed. The deeper overview of each power circle is also presented. All in all, the model proves the complexity and closure of V. Putin’s system. However, it allows to present generalizations of the political system as such. Latest developments and the reshuffle among the members of the closest circle suggest the changes in the system are ongoing, changes which may lead a shift from a “collective Putin” to a “purely authoritarian” management. Therefore, further observations in this regard are required.